2002
DOI: 10.1073/pnas.162095599
|View full text |Cite
|
Sign up to set email alerts
|

The reduction potential of nitric oxide (NO) and its importance to NO biochemistry

Abstract: A potential of about ؊0.8 (؎0.2) V (at 1 M versus normal hydrogen electrode) for the reduction of nitric oxide (NO) to its one-electron reduced species, nitroxyl anion ( 3 NO ؊ ) has been determined by a combination of quantum mechanical calculations, cyclic voltammetry measurements, and chemical reduction experiments. This value is in accord with some, but not the most commonly accepted, previous electrochemical measurements involving NO. Reduction of NO to 1 NO ؊ is highly unfavorable, with a predicted reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
285
0
12

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 352 publications
(315 citation statements)
references
References 46 publications
18
285
0
12
Order By: Relevance
“…However, a recent study by Fukuto, Houk, and co-workers on the reduction potential of the NO/NO -couple using a combination of experimental and computational methods indicated that NO is in fact more difficult to reduce than O 2 . 62 Hence, the main contribution to the observed differences in reactivity of Fe II toward NO and O 2 should be the difference in the strength of the resultant Fe III -NO -and Fe III -O 2 -bonds. In this study, spin-unrestricted DFT calculations with an experimentally optimized level of theory were used to analyze the relative reactivities of the 5C Fe II derivative of 1 toward NO and O 2 ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study by Fukuto, Houk, and co-workers on the reduction potential of the NO/NO -couple using a combination of experimental and computational methods indicated that NO is in fact more difficult to reduce than O 2 . 62 Hence, the main contribution to the observed differences in reactivity of Fe II toward NO and O 2 should be the difference in the strength of the resultant Fe III -NO -and Fe III -O 2 -bonds. In this study, spin-unrestricted DFT calculations with an experimentally optimized level of theory were used to analyze the relative reactivities of the 5C Fe II derivative of 1 toward NO and O 2 ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…The reported E1 0 values have been obtained from Stanbury (1989); Koppenol et al (1992); Buettner (1993); and Bartberger et al (2002).…”
Section: Ascorbate and A-tocopherolmentioning
confidence: 99%
“…Therefore, iNOS is likely to enhance oxidative-nitrosative stress through the formation of ONOO À . ONOO À is much more reactive than NO (Table 1), causes tyrosine nitration and cysteine oxidation in various proteins (Radi et al, 1991), and decomposes to highly toxic free radicals, such as NO 2 K and K OH (Buettner, 1993;Bartberger et al, 2002). Cerebrospinal fluid levels of 3-nitrotyrosine have recently been found to be elevated in children with sepsis (Hamed et al, 2009); 3-nitrotyrosine, which is formed when a tyrosyl radical combines with NO 2 K during tyrosine nitration (Pacher et al, 2007), is relatively stable, and can thus be considered a surrogate molecular 'footprint' of nitrosative stress.…”
Section: No Depletionmentioning
confidence: 99%
“…to proceed via reduction of NO • by SOD, [42] ferrocytochrome c, [43] and ubiquinol, [44] and/or reduction of GSNO by GSH and the alcohol dehydrogenase system. [45][46][47] Several groups have reported that HNO, per se a strong reductant, [48] can trigger reactions of oxidation.…”
Section: Chemical Fate Of No• In Biological Systemsmentioning
confidence: 99%